Correlation study of LINC02609 and SNHG17 as prognostic biomarkers of kidney renal clear cell carcinoma and therapeutic sensitivity based on public data and In Vitro analysis - Xing, Chaoqun; Zou, Weiwei; Li, Yangqin; Zhang, Ti; Yao, Fan; Yao, Zhi-Yong; Xing, Xiao-Liang (Frontiers in Immunology, 2025)
BackgroundCuprotosis, a newly identified form of regulated cell death, has emerged as a potential therapeutic target for cancers. Kidney renal clear cell carcinoma (KIRC) is frequently metastatic at diagnosis, resulting in poor prognosis. This study aimed to identify prognostic biomarkers and construct a risk model to improve survival prediction and guide therapeutic strategies for KIRC patients.MethodsDifferential expression analysis, Cox regression, and risk modeling were performed using transcriptomic and clinical data. The response to immunotherapy and the sensitivity to chemotherapy drugs were analyzed through the Tumor Immune Dysfunction and Exclusion (TIDE) database and the Genomics of Drug Sensitivity in Cancer2 (GDSC2) database. Functional validation of LINC02609 was conducted in renal carcinoma A498 cells using siRNA-mediated knockdown.ResultsLINC02609 and SNHG17 were significantly upregulated in KIRC tissues and independently associated with poor overall survival. The risk model constructed using those two candidate biomarkers (LINC02609 and SNHG17) exhibited high predictive accuracy as measured by the value of area under the curve (AUC). Immune status analysis showed that high- and low-risk KIRC patients exhibited abnormalities immune landscapes. TIDE analysis suggested that the risk model was significantly correlated with multiple immunotherapy-related signatures. RNA-sequencing (RNA-seq) analysis indicated that inhibition of LINC02609 would lead to abnormal activation of the mitogen-activated protein kinases (MAPK) signaling pathway. In vitro experiments confirmed that LINC02609 knockout inhibits the proliferation, migration, and invasion of A498 cells by suppressing the MAPK signaling pathway.ConclusionThe candidate biomarker LINC02609 regulates the progression of renal cell carcinoma through the MAPK signaling pathway. The risk model constructed using LINC02609 and SNHG17 was significantly correlated with multiple immunotherapy-related signatures, suggesting that it might be used for the determination of immunotherapy options in KIRC